Psychiatry interrogated : an institutional ethnography anthology - Burstow, Bonnie (Palgrave Macmillan, 2016)
This edited volume is an anthology of institutional ethnography (IE) inquiries into psychiatry--the first ever to be written. It focuses on a large variety of different geographic locations and constitutes a major contribution to anti/critical psychiatry, as well as institutional ethnography. Themes include the DSM, the use and protection of problematic psychiatric research, the penetration of psychiatry into the workplace. Adding depth and breath, the contributors, while all are schooled in IE, come from a large variety of walks of life, authors including: academics, psychiatric survivors, investigative reporters, activists, nurses, artists, and lawyers--each bringing their own unique expertise/standpoint to bear. The result is an intellectually rigorous book, contributions to several disciplines, ammunition for activism, and a compelling read that cannot be put down.